Interfaces Educação Infantil e Educação Física: estudo bibliométrico de teses e dissertações brasileiras (1993 – 2016) - Silva, Marcia Cristina (2020)
The action field of Physical Education teacher has been increasingly discussed and investigated. Thinking of Early Childhood Education as a stage of Basic Education and in the performance field of this professional, we came to the problem of this research: how the theme of early childhood education is configured in the scientific production of the interface between Childhood Education and Physical Education. To answer this question, a descriptive exploratory research, a qualitative approach, was carried out through a bibliometric study, which aims to identify and analyze the scientific production represented by theses and dissertations defended in these two areas at the Brazilian Digital Library of Theses and Dissertations of the Brazilian Institute of Information in Science and Technologies - BDTD / IBICT in the period of 1993 a 2016. The general objective was to analyze the scientific production on Early Childhood Education in the interface with Physical Education, coming from theses and dissertations defended in postgraduate programs in Education and Physical education in the country, through the BDTD/IBICT. Therefore, the present research was carried out in the BDTD / IBICT website. With the analysis of the works, it was concluded that the most defended themes in the field of Physical Education are: School; Public Policy; Epistemology; Communication and media; Gender; Leisure and Inclusion and Difference. In the field of Education, the privileged themes are: Teacher Training; Curriculum; Education of children from 0 to 6 years old; Reading and writing literacy; Art and education; Environmental Education and History of Education. Regarding the subjects that most appeal to the themes, we have teacher training; the pedagogical practice of the teacher; the game; movement and physical activity as content belonging to Physical Education in Early Childhood Education. The surveys are mostly carried out in the southeast region, with a predominance in the public network. We can see an increase research in Early Childhood Education in the interface with Physical Education master's programs, however, the doctorate programs still with few research on the subject.